Letters written during a short residence in Sweden, Norway, and Denmark - Wollstonecraft, Mary, 1759-1797 (Oxford world's classics (Oxford University Press), 2009)
Letters written during a short residence in Sweden, Norway, and Denmark (1796) is both an arresting travel book and a personal memoir. In it Wollstonecraft describes the sublime landscape and the events and people she encounters. This edition includes reviews, additional letters, and documents on the background to the journey. - ;'If ever there was a book calculated to make a man in love with its author, this appears to me to be the book.'William Godwin, the author's future husband, was not alone in admiring Letters written during a short residence in Sweden, Norway, and Denmark, Wollstonecraf.